2010
DOI: 10.1128/jvi.02017-09
|View full text |Cite
|
Sign up to set email alerts
|

Virus Shedding and Potential for Interspecies Waterborne Transmission of Highly Pathogenic H5N1 Influenza Virus in Sparrows and Chickens

Abstract: To elucidate the role of sparrows as intermediate hosts of highly pathogenic avian influenza H5N1 viruses, we assessed shedding and interspecies waterborne transmission of A/duck/Laos/25/06 in sparrows and chickens. Inoculated birds shed virus at high titers from the oropharynx and cloaca, and infection was fatal. Waterborne transmission from inoculated sparrows to contact chickens was absent, while 25% of sparrows were infected via waterborne transmission from chickens. The viral shedding and susceptibility t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 15 publications
1
29
0
Order By: Relevance
“…being provided with water from cages of acutely infected chickens (Forrest et al, 2010). In contrast to oropharyngeal shedding, cloacal shedding of LPAIV H3N8 among sparrows and starlings was minimal.…”
Section: Discussionmentioning
confidence: 99%
“…being provided with water from cages of acutely infected chickens (Forrest et al, 2010). In contrast to oropharyngeal shedding, cloacal shedding of LPAIV H3N8 among sparrows and starlings was minimal.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have shown that European starlings, sparrows, house finches, great reed warblers and pale thrushes are susceptible to infection with the H5N1 virus (Perkins & Swayne, 2003a, b;Boon et al, 2007;Brown et al, 2009;Forrest et al, 2010;Fujimoto et al, 2010;Liu et al, 2010;Yamamoto et al, 2013). In the present study, two other terrestrial wild bird species, i.e., common reed buntings and brown-eared bulbuls, were shown to be susceptible to recent H5N1 viruses.…”
Section: Resultsmentioning
confidence: 96%
“…Because varying morbidity, mortality and disease signs were observed in experimental infections of the species (Perkins & Swayne, 2003a, b;Boon et al, 2007;Brown et al, 2009;Forrest et al, 2010;Fujimoto et al, 2010;Liu et al, 2010;Yamamoto et al, 2013), the epidemiologic role of passerine birds in the spread of HPAI virus is still unclear. In this study, to investigate the susceptibility of wild passerines that are widely distributed in Asian countries, we therefore inoculated three species of these birds, common reed buntings, pale thrushes and brown-eared bulbuls, with H5N1 HPAI virus strains isolated from wild birds.…”
Section: Introductionmentioning
confidence: 98%
“…The spiking of faeces (dry and wet) was done in order to ensure a final virus concentration of around 10 6 EID 50 /ml, which is often shed by the infected chickens in the faeces [8]. Briefly, both dry and wet faeces were spiked with the original virus (EID 50 10 10.33 /ml, diluted 1:100) in the ratio of 1 part diluted virus: 1 part faeces and triturated with mortar pestle to ensure proper mixing.…”
Section: Spiking Of the Virus In The Faeces And Titration Of Virus Inmentioning
confidence: 99%